Perubahan Karakteristik Fisik Model Minuman Biji Chia Akibat Proses Pemanasan, Perubahan pH, Penambahan Gula dan Garam - Feri Kusnandar; Asep Safari; Elvira Syamsir (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Chia seed has high nutritional contents and bioactive components potentially used as a food ingredient in beverage products. This study aimed to evaluate the changes of physical characteristics (water absorption capacity or DIA, seed thickness, and viscosity) of chia seeds in beverage models due to heating temperature (70, 90oC) and time (1, 2 hours), pH (3, 5, 7), sugar, (0, 15% ) salt salt (1% KCl and 1% CaCl2) in 3% and 5% chia seeds. The results showed that the pH of the beverage model affected the DIA, viscosity and thickness of the chia seed gum capsules. The higher the pH, the greater the DIA, thickness and viscosity. Sugar concentration and heating time did not affect the physical characteristics of chia seeds, whereas the heating temperature only had a significant effect on pH 3. Addition of CaCl2 1% caused the increase of DSA for approximately twice compared to that of KCl 1%. The addition of chia seeds up to 5% in salt solutions did not affect the DIA.